Pneumomediastinum, Pneumoperitoneum, Pneumothorax and Cervical Subcutaneous Emphysema Following Diagnostic Colonoscopy: A Case Report (Annals of Medical Research, 2021)
None
Keywords: Diagnostic Colonoscopy, Colonic Perforation, Pneumomediastinum, Pnömoperitoneum, Subcutaneous Emphysema